Lynx rufus - Don E. Wilson; Russell A. Mittermeier (Lynx Edicions, 2009)
21. Bobcat Lynx rufus French: Lynx roux / German: Rotluchs / Spanish: Lince rojo Other common names: Red Lynx, Bay Lynx, Cat Lynx Taxonomy. Felis rufus Schreber 1777, “Provinz New York in Amerika”. Taxonomists currently recognize twelve subspecies. Some studies, however, suggest that the actual number of subspecies may be less, and that modern taxonomy should be reassessed. Subspecies and Distribution. L. r. rufus Schreber, 1777 — C Canada (Saskatchewan, Manitoba & W Ontario) and C & NE USA (North Dakota, South Dakota, Nebraska, Kansas, Oklahoma, Arkansas, Iowa, Illinois, Indiana, Ohio, Pennsylvania, New York, New Jersey, Delaware, Maryland, Virginia, West Virginia, Kentucky & Tennessee). L. r. bailey: Merriam, 1890 — SW USA and NW Mexico. L. r. californicus Mearns, 1897 — SE USA (California). L. r. escuinapaeJ. A. Allen, 1903 — Pacific coast and C Mexico. L. r. fasciatus Rafinesque, 1817 = NW coast of USA. L. r. floridanus Rafinesque, 1817 — SE USA. L. r. gigas Bangs, 1897 — E Canada (Maritime Provinces), and NE USA (New England). L. r. oaxacensis Goodwin, 1963 — S Mexico (Oaxaca). L. r. pallescens Merriam, 1899 — SW Canada (British Columbia & Alberta), and W USA (Montana, Wyoming, Colorado, Utah, Nevada & Idaho). L. r. perunsularis Thomas, 1898 — NW Mexico (Baja California). L. r. superiorensis Peterson & Downing, 1952 — S Canada (Ontario), and N USA (Michigan, Wisconsin & Minnesota). L. r. texensis J. A. Allen, 1895 — S USA (Texas), and NE Mexico (Tamaulipas, Nuevo Leon & Coahuila). Descriptive notes. Medium-sized, short-tailed cat. Head-body length is 65-105 cm, and tail length is 9-11 cm. Adult males average 8.9-13. 3 kg. Adult females average 5.8-9. 2 kg. Cranial measurements and adult weights indicate a size gradient that decreases with latitude. Kittens weigh 0.3-0. 4 kg at birth. The pelage contains various shades of buff-brown, and is mottled with dark spots and streaks. Some may have a rufous tint to the pelage. Cranial furis streaked with black, and the back of the ...